The Duty of Efficiency & Generative AI Pedagogy - Megan Boyd; Brian Frye (Washington University Journal of Law and Policy, 2025)
The emergence of generative artificial intelligence (generative AI) promises to transform the legal profession by improving efficiency, yet its adoption has been hindered by several obstacles. Courts have imposed restrictions on AI use, and law schools have been slow to integrate AI training into their curriculum. The legal profession’s reluctance to embrace AI stems from concerns about accuracy, confidentiality, and professional responsibility. This Article contends that law schools must play a proactive role in preparing students for incorporated AI in their practice. It examines the ethical obligations of lawyers regarding AI use, evaluates reactionary regulations, and proposes a pedagogical framework that equips students with the skills necessary to leverage AI effectively. The legal profession must acknowledge AI’s growing role and ensure that future lawyers are trained to use it responsibly and strategically.
Keywords: AIandLaw; LegalTechEducation; EthicsInAI